No more secrets?: Policy implications of commercial remote sensing satellites - FLORINI, Ann (Institutional Knowledge at Singapore Management University, 1999)
Ever since the earliest satellites and astronauts started taking pictures of the Earth from space nearly four decades ago, those images have inspired excitement, introspection, and, often, fear. Like all information, satellite imagery is in itself neutral. But satellite imagery is a particularly powerful sort of information, showing both comprehensive vistas and surprising detail. Its benefits can be immense—but so can its costs. The same images that remind us that we all share a fragile planet also enable those who have the images to more accurately aim their weapons at adversaries near and far.